Use of nutritional devices in Cornelia de Lange syndrome: Data from a large Italian cohort. Issue 9 (21st September 2018) - Decimi, Valentina; Parma, Barbara; Panceri, Roberto; Fossati, Chiara; Mariani, Milena; Russo, Silvia; Gervasini, Cristina C.; Cheli, Maurizio; Cereda, Anna; Selicorni, Angelo
Abstract : Cornelia de Lange syndrome (CdLS) is a genetic condition characterized by intellectual disability, peculiar facial dysmorphisms, multiorgan malformations, and growth problems. Majority cases of CdLS are caused by mutations in genes of Cohesin pathway. Although feeding problems are a well‐known feature, no specific data have been published about the use of nutritional devices. We analyzed use, type, time of introduction, and duration of nutritional devices in 73 CdLS patients. In total, 29/73 (40%) used a device; nasogastric tube (NGT) in 28/73 (38%) and percutaneous endoscopic gastrostomy (PEG) in 7/73 (10%). NGT was placed during the first days/weeks of life. 19/28 (68%) maintained it for less than 3 months, 7/28 (25%) for a period between 3 and 12 months, while 2/28 (7%) for more than 1 year. PEG was placed within the first year in 4/7 (57%) and removed in two patients after 4 years These data have been matched with a wide number of genetic and clinical variables. Presence of upper limb malformations is positively correlated with the need of a device. From the opposite side, the use of a device positively correlates with a more severe prognosis as regard growth, intellectual development and disease severity. Our data show that nutritional devices are frequently used by CdLS patients, also if the majority of them (93.1%) succeed with time in achieving a normal oral nutrition. Finally, the need, the type of device used and the duration of NGT or/plus PEG can be considered a further sign of worse prognosis of the disease itself.